Global Business Cycles. - Kose, M. Ayhan (IMF Working Papers., 2008)
This paper analyzes the evolution of the degree of global cyclical interdependence over the period 1960-2005. We categorize the 106 countries in our sample into three groups-industrial countries, emerging markets, and other developing economies. Using a dynamic factor model, we then decompose macroeconomic fluctuations in key macroeconomic aggregates-output, consumption, and investment-into different factors. These are: (i) a global factor, which picks up fluctuations that are common across all variables and countries; (ii) three group-specific factors, which capture fluctuations that are comm.